Some Classes of Difference Sequence Spaces of Fuzzy Real Numbers Defined by Orlicz Function - Binod Chandra Tripathy; Stuti Borgohain (Advances in Fuzzy Systems, 2011)
We introduce the classes of generalized difference bounded, convergent, and null sequences of fuzzy real numbers defined by an Orlicz function. Some properties of these sequence spaces like solidness, symmetricity, and convergence-free are studied. We obtain some inclusion relations involving these sequence spaces.